2023
DOI: 10.1002/phar.2760
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam‐associated behavioral adverse events in neurocritical care patients

Abstract: Levetiracetam is an antiseizure drug commonly utilized in the neurocritical care (NCC) environment for the treatment of seizures, status epilepticus, and as a prophylactic therapy in certain situations.Levetiracetam's exact mechanism of action is unknown; however, its main antiseizure effect is proposed to be neurotransmitter modulation through binding to synaptic vesicle glycoprotein 2A. 1,2 Levetiracetam has also been shown to have modulating effects at the α-amino-3-hydroxy-5-methyl-4-isoxazole propionic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Additionally, prescribers may have overestimated the potential risks associated with higher doses. Although LEV is generally well tolerated (11, 22), behavioral abnormalities (agitation, delirium, anxiety) have been reported in up to 46% of patients, although it is unclear if these events represent a drug side effect or are related to the primary brain injury (23). To this point, the PEACH trial found no difference in serious adverse events, depression, or anxiety in patients who received LEV 500 twice daily compared to placebo (6).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, prescribers may have overestimated the potential risks associated with higher doses. Although LEV is generally well tolerated (11, 22), behavioral abnormalities (agitation, delirium, anxiety) have been reported in up to 46% of patients, although it is unclear if these events represent a drug side effect or are related to the primary brain injury (23). To this point, the PEACH trial found no difference in serious adverse events, depression, or anxiety in patients who received LEV 500 twice daily compared to placebo (6).…”
Section: Discussionmentioning
confidence: 99%
“…As levetiracetam is associated with behavioral adverse reactions, possibly due to its potential inhibitory effects on the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor, brivaracetam has attracted attention because it may have fewer behavioral side effects given that it does not appear to work via this mechanism. 26 However, there is less evidence supporting its use in treating SE. The dosing for brivaracetam for SE is not well defined, but a loading dose of 200 mg followed by maintenance doses of 50 to 100 mg twice daily is considered reasonable at this urgent treatment stage.…”
Section: Updates On Benzodiazepinesmentioning
confidence: 99%
“…Antiseizure medications and dosing in status epilepticus5,6,26,[29][30][31][32][33][34][35][36][37][38]61 26. However, there is less evidence supporting its use in treating SE.…”
mentioning
confidence: 99%
See 1 more Smart Citation